Surgical management of tracheal chondrosarcoma. Issue 5 (3rd September 2022) - Rotolo, Nicola; Cattoni, Maria; Nardecchia, Elisa; De Maio, Silvia; Franzi, Francesca; Pettenon, Fabiana; Imperatori, Andrea
Abstract: Background: Tracheal chondrosarcoma is an extremely rare, slow-growing, malignant tumour. This study aims to analyze the cases of tracheal chondrosarcoma published in the literature and our case report, in order to better define tracheal chondrosarcoma management. Methods: A systematic review of the English literature was carried out for fully described tracheal chondrosarcoma cases. Additionally, we reported a new case of a 58-year-old man undergoing tracheal resection and reconstruction for tracheal chondrosarcoma. Results: To date, 30 cases were published. This tumour predominantly involved male patients (93%; median age: 65 years), generally conditioning dyspnoea and cough. Most of the patients underwent tracheal resection with end-to-end anastomosis, without recurrence (median follow-up: 2 years). Tumours endoscopically treated recurred in half cases. Conclusion: Tracheal resection is the treatment of choice for chondrosarcoma, with an excellent prognosis. Endoscopic treatment and/or radiotherapy should be indicated for patients unfit for surgery.